PENGARUH KOMBINASI TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) DAN RENDAM KAKI AIR HANGAT DENGAN CAMPURAN JAHE MERAH TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI - Risfinda, Risfinda; Bayhakki, Bayhakki; Amir, Yufitriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
High blood pressure (hypertension) can quietly damage the body for years before symptoms develop. Roughly half the people with untreated hypertension die because of heart disease related to poor blood flow. Therefore, nonpharmacological treatment is a great way to recirculate blood and warmth. With combination of SEFT therapy and hydrotherapy, this research was aimed to explore the effect of SEFT and hydrotherapy with a mixture of red ginger to reduce high blood pressure in patients at Puskesmas Payung Sekaki. Quasi Experimental were used in this study using non-equivalent control group approach. Samples were 36 respondents (divided equally into 2 groups) recruited using purposive sampling technique. The intervention group received SEFT intervention combined hydrotherapy for 20 minutes per day in 6 consecutive days, while the control group was not given any treatment. The analysis used was univariate analysis to see frequency and bivariate analysis with dependent t test and independent t test. The result of statistical test showed that there was significant difference of blood pressure before and after intervention with p value 0,000 (<0,05). The results showed that the combination of SEFT therapy and hydrotherapy with a mixture of red ginger can lower blood pressure patients with hypertension. The results recommend SEFT and hydrotherapy as an adjunctive therapy to decrease blood pressure.Keywords: Blood pressure, hydrotherapy, hypertension, SEFT